Reservoir Densification, Pressure Evolution, and Natural Gas Accumulation in the Upper Paleozoic Tight Sandstones in the North Ordos Basin, China - Ren Wang; Kai Liu; Wanzhong Shi; Shuo Qin; Wei Zhang; Rong Qi; Litao Xu (Energies, 2022)
The vague understanding of the coupling relationship among natural gas charging, reservoir densification, and pressure evolution restricted the tight gas exploration in the Lower Shihezi Formation of the Hangjinqi area, north Ordos Basin. In this study, the quantitative porosity evolution model, the pressure evolution process, and the natural gas charging history of tight sandstone reservoirs were constructed by integrated investigation of the reservoir property, the thin section, SEM and cathode luminescence observations, the fluid inclusion analysis and the 1D basin modeling. The results show that the compaction and cementation reduced the primary porosity by 21.79% and 12.41%, respectively. The densification of the reservoir occurred at circa 230 Ma, which was before the natural gas charging time from 192 to 132 Ma. The paleo-overpressure within the tight reservoirs occurred since the Middle Jurassic with the pressure coefficients between 1.1 and 1.55. The continuous uplifting since the Late Cretaceous resulted in the under- and normal-pressure of the Lower Shihezi Formation with the pressure coefficients ranging from 0.67 to 1.05. The results indicate that the densification of the reservoirs was conducive to the formation of paleo-pressure produced by gas generating. The gas predominantly migrated vertically, driven by gas expansion force rather than buoyance and displaced the pore water in the reservoirs near source rocks.